Paramedics A Survey of the Issues - Lave, Judith R.; Carnegie-Mellon Univ., Pittsburgh, PA. Graduate School of Industrial Administration ([Washington, D.C.] : Distributed by ERIC Clearinghouse, 1971)
This report examines some of the issues surrounding the use of paramedic personnel. Following background information, emphasis is placed on programs and demonstration projects, training programs, the potential role of paramedics, the potential functions of paramedics, quality of care, acceptance of paramedics by patients and other personnel, the economics of paramedics, productivity, reimbursement policies, education and career mobility, and legal issues. Each issue is discussed in relation to relevant literature. An extensive bibliography is included. (Author/MJM)
Sponsoring Agency: Department of Health , Education, and Welfare, Washington., DC. Office of the Secretary.
ERIC Note: Revised study.
Educational level discussed: Higher Education.
May also be available online. Address as at 14/8/18
Microfiche.
Keywords: Allied Health Occupations; Health Occupations; Health Personnel; Higher Education; Medical Services